Dilema Psikologis dan Hukum: Studi Kasus Pencurian dengan Pemberatan oleh Anak di Bawah Umur - Muhaammad Luthfi Firjatullah; Muhammad Natsir; Dian Anggreni Thamrin; Arini Asriyani; Fikry Fathurrahman (Jurnal Litigasi Amsir, 2025)
This study analyses the application of the law by judges in sentencing minors who commit the crime of theft with aggravation (case study of Verdict No. 2/Pid.Sus-Anak/2023/PN Pre). The research highlights how judges balance judicial considerations, including examining witnesses, defendants' statements, evidence, and prosecutors' indictments based on Pasal 363 KUHP, with non-juridical considerations such as the child's psychological condition, environmental factors, as well as aggravating and mitigating aspects. The results of the study show that judges not only focus on fulfilling criminal elements, but also pay attention to the protection and development of children as perpetrators. In this case, the judge decided on a criminal sanction of imprisonment for 3 months, taking into account justice, deterrent effects, and rehabilitation efforts for the child. These findings affirm the importance of a holistic approach in handling child criminal cases, so that substantive justice and the protection of children's rights are maintained